2017
DOI: 10.1002/2327-6924.12424
|View full text |Cite
|
Sign up to set email alerts
|

HIV screening intentions, behaviors, and practices among nurse practitioners

Abstract: Background and purpose HIV/AIDS is a significant public health issue for individuals living in the United States. Federal agencies and key stakeholders recommend routine HIV/AIDS screening among individuals aged 13–64 of age, yet few studies focus on the nurse practitioner's (NP) perspective. The purpose of this study was to examine routine HIV screening intentions, behaviors, and practices using a national sample of NPs. Methods Cross‐sectional study utilizing a random sample of 600 NPs from the American Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of this secondary analysis indicated that NPs are not offering HIV testing in line with recommendations from national organizations. Consistent with previous research (Anaya et al, 2008;Chin et al, 2013;McNaghten et al, 2013;Shirreffs et al, 2012;Sutherland & Spencer, 2017), NPs reported low rates of HIV screening and inconsistent screening policies that varied across practices.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this secondary analysis indicated that NPs are not offering HIV testing in line with recommendations from national organizations. Consistent with previous research (Anaya et al, 2008;Chin et al, 2013;McNaghten et al, 2013;Shirreffs et al, 2012;Sutherland & Spencer, 2017), NPs reported low rates of HIV screening and inconsistent screening policies that varied across practices.…”
Section: Discussionsupporting
confidence: 83%
“…Chin et al (2013) discovered that among 101 individuals newly diagnosed with HIV, 72 had $ 1 prior visit and 47 had $2 visits by a health care provider in the year before their diagnosis. A study done by Sutherland and Spencer (2017) found that only 25% of 141 nurse practitioners (NPs) reported routine HIV screening behaviors among NPs practicing in one of the eight health care settings, and nearly 15% reported screening no patients. Two studies conducted in the southern United States, the epicenter of the HIV epidemic, also reported low screening rates.…”
Section: Introductionmentioning
confidence: 99%